Gonadectomy in Mito-Ob mice revealed a sex-dimorphic relationship between prohibitin and sex steroids in adipose tissue biology and glucose homeostasis - Yang Xin Zi Xu (Biology of Sex Differences, 2018)
Abstract Background Recently, we have developed a novel transgenic mouse model by overexpressing prohibitin (PHB) in adipocytes, which developed obesity due to upregulation of mitochondrial biogenesis in adipocytes, hence named “Mito-Ob.” Interestingly, only male Mito-Ob mice developed obesity-related impaired glucose homeostasis and insulin sensitivity, whereas female Mito-Ob mice did not. The observed sex differences in metabolic dysregulation suggest a potential involvement of sex steroids. Thus, the main aim of this study is to investigate the role of sex steroids on the overall phenotype of Mito-Ob mice through gonadectomy, as well as direct effect of sex steroids on adipocytes from Mito-Ob mice in vitro. Methods Mito-Ob mice and wild-type CD-1 mice were gonadectomized at 12 weeks of age. Age- and sex-matched sham-operated mice were used as controls. Body weight, white adipose tissue, glucose tolerance, and insulin sensitivity were analyzed 3 months post-surgery. Differentiation of adipocytes isolated from female and male Mito-Ob mice were studied with and without sex steroids. Results Gonadectomy significantly reduced body weight in Mito-Ob mice compared with sham-operated mice, whereas the opposite trend was observed in wild-type mice. These changes occurred independent of food intake. A corresponding decrease in adipose tissue weight was found in gonadectomized Mito-Ob mice, but depot-specific differences were observed in male and female. Gonadectomy improved glucose tolerance in male wild-type and Mito-Ob mice, but the effect was more pronounced in wild-type mice. Gonadectomy did not alter insulin sensitivity in male Mito-Ob mice, but it was improved in male wild-type mice. In primary cell cultures, testosterone inhibited adipocyte differentiation to a lesser extent in male Mito-Ob preadipocytes compared with the wild-type mice. On the other hand, preadipocytes from female wild-type mice showed better differentiation potential than those from female Mito-Ob mice in the presence of 17β-estradiol. Conclusions PHB requires sex steroids for the development of obese phenotype in Mito-Ob mice, which differentially affect glucose homeostasis and insulin sensitivity in male and female. It appears that PHB plays sex- and adipose depot-specific roles and involves additional factors. In vitro studies suggested that PHB differently influenced adipocyte differentiation in the presence and absence of sex steroids. Overall, this study along with available information in the literature indicated that a multifaceted relationship exists between PHB and sex steroids, which may work in a cell/tissue type- and sex-specific manner.